Comparison of three different pretreatment methods for blood RNA extraction. Issue 1 (December 2019) - Zhang, Jiayi; Xu, Qiannan; Chen, Liqin; Liu, Xiling; Li, Chengtao
Abstract: In forensic genetics, the RNA expression profiles obtained from forensic casework can be utilized to identify specimens' biological features, such as the origin of body fluids, age estimation, etc. However, RNA is grossly susceptible to external factors and this characteristic leads to its low integrity and concentration, which make the ideal RNA expression profiles hard to be obtained. Thus, the methods of sample pretreatment and storage play a pivotal role in forensic RNA researches. In this study, we evaluated three different pretreatment methods for their effects on the quality of RNA extracted from peripheral blood by detecting the RNA yield, concentration and integrity. Results illustrated that the RNA pretreated by the preservation solution and stored at −80 °C had the highest quality.